Penerapan Skala DIVA Terhadap Keberhasilan Pemasangan Akses Intravena Pada Pasien Pediatrik - Yani Setiasih; Murtiningsih, Murtiningsih; Inayah, Iin (Yayasan Mandar Indonesia, 2022)
Installation of intravenous access in pediatric patients is a challenge. The DIVA scale is one of the predictive tools for determining difficult intravenous access. The purpose of this literature review is to analyze research articles on the application of the DIVA scale to determine difficult intravenous access in the installation of intravascular access in pediatric patients. This literature search was carried out on electronic databases such as Pubmed, Proquest and Google Scholar. Articles were selected according to inclusion and exclusion criteria. Inclusion criteria are articles published in 2016 – 2021, articles can be accessed in full text with the subject of the DIVA scale in pediatrics. Based on a literature review of 3 articles, it was found that the DIVA scale can be used to detect difficult veins in the installation of intravenous access in pediatric patients. Implementing the DIVA scale is beneficial in reducing the amount of effort required for the installation of intravenous access. The conclusion from this literature study is that the DIVA scale can be modified and validated according to where the DIVA scale is used. DIVA score 4 increases failure of intravenous access in the first trial in pediatric patients.